Comparative Results of DAS28 and Quality of Life in Patients with Rheumatoid Arthritis and Fibromyalgia - Filiz Sivas; Lale Akbulut Aktekin; Filiz Eser; Fatma Gül Yurdakul; Ergun Öksüz; Kürşat Özoran; Hatice Bodur (Archives of Rheumatology, 2010)
Objective: In the present study, we compared Disease Activity Score 28-4v (DAS28-4v) and quality of life by using Short Form-36 (SF-36) in patients with rheumatoid arthritis (RA) and fibromyalgia (FM). Materials and Methods: The swollen joint count (SJC) and the tender joint count (TJC) of 79 patients with RA and 34 patients with FM, the Patient Global Assessment (PGA) with 100 mm visual analog scale (VAS), and erythrocyte sedimentation rates (ESR) were recorded and DAS28-4v scores were calculated. The quality of life in both groups was evaluated by using SF-36. Result: The mean DAS28-4v score of the RA group was 3.63±1.52 (0.77-7.40) and of the FM group was 2.42±0.73 (0.57-3.86), and the difference between groups was statistically significant (p<0.001). In the Principal Component Analysis (PCA), in the RA group, the components that most affected DAS28-4v were TJC and SJC, while in the FM group, these were SJC and PGA. Significant differences were detected between the two groups in most SF-36 subgroups, except in the general mental health, social functioning and social role limitation subgroups. In the FM group, the physical function subgroup was significantly higher (p<0.001). Conclusion: Although there is no objective injury such as inflammation or joint damage, FM can decrease the quality of life to the same extent as RA. FM, which is a non-inflammatory disease, can cause high rates in DAS28-4v due to the fact that there are many subjective complaints such as the TJC and the PGA. The intervening infections during the evaluation of disease activity in RA or concomitant diseases like FM might cause fluctuations in the DAS28-4v score. (Turk J Rheumatol 2010; 25: 179-83 )